Timeliness of Keyboarding Instruction as Perceived by Business Educators in Ondo and Ekiti States, Nigeria - Adebayo, Aina Matthew; Igbinedion, V. I. (American Journal of Creative Education, 2019)
The rate at which pupils are learning how to key-in and make use of the keyboard for typing without adequate consideration for acquisition of appropriate skills for effective keyboarding has become worrisome in recent times. This study determined the appropriate time for learning keyboarding in Nigerian educational system as perceived by business educators in Ondo and Ekiti States. Three research questions were raised to guide the study. Survey research design was employed. The population of the study was made up of 98 business educators in On do and Ekiti states. The entire population was studied. The instrument designed for the study consisted of 31 items which was validated by Business Education and Test and Measurement experts. The validated instrument was subjected to reliability test, using split-half method. The data collected were analysed using Pearson product moment correlation formula and a coefficient of 0.83 was obtained. Mean and standard deviation were used to answer the research questions. The findings of the study revealed that keyboarding skills cannot be effectively mastered at the lower and middle basic levels of Nigerian education system, among others. It was concluded that keyboarding skills are best acquired at the upper basic level where students would have developed appropriate cognitive and psychomotor skills. Thus, it was recommended that manipulative keyboarding skills should not be incorporated into the curriculum of lower and middle basic levels of the nation’s educational system, among others.